Translating Popular Film - O'Sullivan, C. author. aut Link
XI, 243 p.
Keywords: A ground-breaking study of the roles played by foreign languages in film and television and their relationship to translation. The book covers areas such as subtitling and the homogenising use of English, and asks what are the devices used to represent foreign languages on screen?